PENERAPAN MODEL PEMBELAJARAN COOPERATIF INTEGRATED READING COMPOTITION (CIRC) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS IVSD 64/1 MUARA BULIAN - Aulia Rakhmi; Ahmad Syarif; Suci Hayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students’ reading comprehension skills through the implementation of the Cooperative Integrated Reading Composition (CIRC) learning model. This research is a classroom action research (CAR) conducted in two cycles, each consisting of two meetings. The subjects were 18 fourth-grade students of SD 64/1 Muara Bulian. Data were collected through observation, tests, interviews, and documentation. The results showed that prior to the implementation of the CIRC model, students' reading comprehension ability was still low, with an average class percentage of 50%, due to factors such as low motivation, lack of reading interest, and the use of conventional teaching methods. The learning process using the CIRC model was carried out in five stages: orientation, organization, concept introduction, publication, and reinforcement or reflection. After applying the CIRC model, there was a significant improvement in students’ reading comprehension skills. The average score increased from 50% in the pre-action stage to 55% in cycle I meeting 1, 61% in meeting 2, 74% in cycle II meeting 1, and reached 82% in cycle II meeting 2. This improvement indicates that the CIRC learning model is effective in helping students understand reading content, identify main and supporting ideas, determine statements relevant to the text, and draw conclusions independently.